Checking the manipulation checks in information security research. (9th March 2015) - Marett, Kent
Abstract : Purpose: – An increasing amount of attention is being paid to the human side of information security programs, leading to research designs that require the manipulation of study variables. The purpose of this paper is to highlight a traditional assessment of such designs, the manipulation check, and examine how its absence can undermine otherwise solid research efforts. Design/methodology/approach: – This paper reviews literature from the fields of research methods, organizational behavior and information systems for extant perspectives and viewpoints on manipulation checks, which are then brought into the realm of information security research. Findings: – The possible risks involved with failing to perform manipulation checks are discussed, which include a possibility of making Type II errors. The paper provides further insight on the timing, method and manner in which manipulation checks can be performed. Originality/value: – A disappointing number of research articles in the area of information security fail to report manipulation checks when they should. This paper seeks to remind researchers to perform this vital assessment and to use the results accordingly.